EDUCATING CHILDREN WITH HEART AND SELF-QUALITY: IMPLICATIONS OF KI HADJAR DEWANTARA'S THINKING ON PRIMARY SCHOOL CHARACTER EDUCATION - Yusuf Siswantara; Ace Suryadi; Mupid Hidayat; Ganjar Muhammad Ganeswara; Asnita Sirait (Jurnal Cakrawala Pendas, 2023)
The problem of bad behavior of the younger generation in the form of juvenile delinquency is a major concern in character education in elementary schools. Using qualitative methods, this study aims to raise character education in the educational paradigm of Ki Hadjar Dewantara as a fundamental solution to the problem of juvenile delinquency. The results showed that both the inner interiority in Neng, Ning, Nung, and Nang, the person (will and heart) who is "antêp, mantêp, têtêp," the child's attitude that is "Ngandel, Kandêl, Kêndêl, Bandêl" (attitude area), and the educational method "Among" with spirit: "Ing Ngarsa Sung Tulada, Ing Madya Mbangun Karsa, Tut Wuri Handayani" can be an effective choice in developing character education. The recommendation for future research is to evaluate the effectiveness of the "Among, Momong, Ngemong" method by focusing on the factors of influence of family environment, peers, and school culture. The concrete solution for primary school education is the preparation of a curriculum that is more focused on building student character by incorporating eastern values and moral education as well as training and developing teacher competencies in carrying out character education in the daily learning process. Masalah perilaku buruk generasi muda dalam bentuk kenakalan remaja menjadi perhatian utama dalam pendidikan karakter di sekolah dasar. Dengan menggunakan metode kualitatif, penelitian ini bertujuan untuk mengangkat pendidikan karakter dalam paradigma pendidikan Ki Hadjar Dewantara sebagai solusi mendasar atas masalah kenakalan remaja. Hasil penelitian menunjukkan bahwa karakter baik dalam interioritas batin dalam Neng, Ning, Nung, dan Nang, pribadi (kehendak dan hati) yang "antêp, mantêp, têtêp," sikap anak yang "Ngandel, Kandêl, Kêndêl, Bandêl" (area sikap), dan metode pendidikan “Among” dengan semangat: “Ing Ngarsa Sung Tulada, Ing Madya Mbangun Karsa, Tut Wuri Handayani” dapat menjadi pilihan efektif dalam mengembangkan pendidikan karakter. Rekomendasi untuk penelitian selanjutnya adalah untuk mengevaluasi efektivitas metode "Among, Momong, Ngemong" dengan memfokuskan pada faktor-faktor pengaruh lingkungan keluarga, teman sebaya, dan budaya sekolah. Solusi konkret untuk pendidikan sekolah dasar adalah penyusunan kurikulum yang lebih terfokus pada pembentukan karakter siswa dengan memasukkan nilai-nilai ketimuran dan pendidikan moral serta pelatihan dan pengembangan kompetensi guru dalam melaksanakan pendidikan karakter dalam proses pembelajaran sehari-hari.